2017
DOI: 10.3390/ijms18102133
|View full text |Cite
|
Sign up to set email alerts
|

3,5,6,7,8,3′,4′-Heptamethoxyflavone Ameliorates Depressive-Like Behavior and Hippocampal Neurochemical Changes in Chronic Unpredictable Mild Stressed Mice by Regulating the Brain-Derived Neurotrophic Factor: Requirement for ERK Activation

Abstract: We previously reported that the subcutaneous administration of 3,5,6,7,8,3′,4′-heptamethoxyflavone (HMF), a citrus polymethoxyflavone, attenuated depressive-like behavior and increased the expression of brain-derived neurotrophic factor (BDNF) in the hippocampus of a corticosterone-induced depression-like mouse model. We herein demonstrated that (1) HMF was detectable in the brain 10 and 30 min after its oral administration, (2) orally administered HMF improved chronic unpredictable mild stress (CUMS)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Truth be told, it has as of late been exhibited that orally administered 3,5,6,7,8,3′,4′-heptamethoxyflavone (9) is beneficial for the upregulation of BDNF in the hippocampus via the ERK1/2/MAP system. These information ought to be identified with the antidepressant effects of this compound [ 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…Truth be told, it has as of late been exhibited that orally administered 3,5,6,7,8,3′,4′-heptamethoxyflavone (9) is beneficial for the upregulation of BDNF in the hippocampus via the ERK1/2/MAP system. These information ought to be identified with the antidepressant effects of this compound [ 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…BDNF is the most widely-distributed neurotrophic factor in the central nervous system and, importantly, activated CREB directly regulates the transcription of BDNF [ 38 ]. Increased expression of BDNF in the hippocampus and cortex produces an antidepressant-like effect in both corticosterone and chronic unpredictable mild stress-induced depression-like animal models [ 39 ]. In order to investigate the effect of FCPR03 on the expression of BDNF, LPS-treated mice were pretreated with 0.5 and 1 mg/kg FCPR03, and BDNF was detected by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…In our present study, we found that BDNF expression significantly increased after CPA in parallel with a decreased expression in ERK and no changes in CREB or pro‐BDNF expression in DG and BLA. Although it has been demonstrated a dual and directional regulatory mechanism between BDNF/ERK/CREB (for review, see Sawamoto et al), other factors could be implicated in the modulation of the BDNF pathway. It is known that BDNF undergoes both retrograde and anterograde transport, so BNDF could be transported from VTA to BLA or DG, without changes in pCREB and ERK in these areas.…”
Section: Discussionmentioning
confidence: 99%